Da leitura de palavras para textos infantis: inteligibilidade, fluência e nomeação em crianças com implante coclear - Rique, Luciana Degrande [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Considering the extension of the paradigm of equivalence in hear impaired and cochlear implanted children the propoise of this study was to teach conditional relations between auditive and visual stimuli, including dictated word, printed word and picture, and then testing the emergence of equivalence classes and expressive verbal repertory as reading of words and picture nomination. Thus, the effects of this teaching procedure was verified during tests of reading children's books over the intanbibility and fluency of this reading performance. The participants was three children with deep-sever hearing, bilateral, pre-lingual hear impairment, cochlear implant users. All of them was male, between seven and ten years old and attending elementary shcool. The routines of teaching and testing were conducted with three books from the book collection Coleção Estrelinha 1 and a MacBook that presented the teaching programs and recorded the participants performance. The general design was a Pre-test of book reading and a series of selection and vocalization tasks from a list of words retrieved from the same books. The word teaching were conducted with multiple baseline: After the teaching of the audio-visual conditional relations between dictated and printed word (AC), dictated word and picture (AB) through matching to sample (MTS), the participants were exposed to tests of equivalence classes formation (BC and CB) and vocalization as word reading (CD) and picture nomination (BD) with the words from book 1. The reading accuracy and fluency of the three books were evaluated; the same procedure occurred with book 2 and 3. The participants learned the training word relations, attested the formation of equivalence classes and showed increased correspondence point at their performance at the word of vocalization. As for the book reading, there was an increase at the percentage of hits at the total readings of the books and of the training words after...

Considerando as extensões do paradigma da equivalência em pessoas com deficiência auditiva e implante coclear o presente estudo teve como objetivo ensinar relações condicionadas auditivo-viauais envolvendo palavra ditada, palavra impressa e figura, testar a emergência de classes de equivalência e de repertório verbal expressivo, como leitura de palavras e nomeação de figuras. Ainda verificou-se os efeitos deste ensino sobre a leitura de livros infantis, em relação à inteligibilidade e fluência na leitura. Participaram três crianças com deficiência auditiva severa-profunda, bilateral, pré-lingual e usuárias de implante coclear; todas do sexo masculino, entre sete e dez anos de idade, frequentando o Ensino Fundamental. As rotinas de ensino e testes foram conduzidas com três livros da Coleção Estrelinha 1 e um MacBook que apresentava as tarefas e registrava o desempenho dos participantes. O delineamento geral consistiu de um Pré-teste de leitura dos livros e de relações envolvendo repertório de seleção e vocalização de uma lista de palavras dos mesmos que selecionou estímulos para dois conjuntos. O Ensino dos conjuntos de palavras dos livros foram conduzidos em Linha de Base Múltipla: após o ensino das relações condicionadas auditivo-visuais palavra ditada e palavra impressa (AC) e palavra ditada e fugura (AB) por matching to sample (MTS), testes de formação de classes de equivalência (BC e CB) e de vocalização como leitura (CG) e nomeação (BD) com as palavras do livro 1, a precisão de leitura e fluência em todos os três livros também eram avaliadas, o mesmo procedimento ocorreu com livros 2 e 3. Os participantes aprenderam as relações ensinadas, atestaram a formação de classes de equivalência e aumentaram a correspondência ponto a ponto em seus desempenhos em tarefas de vocalização (BD). Quanto à leituar dos livros, houve um aumento nas porcentagens de acertos na leitura total dos livros...
The reading of the words for child texts: intangibility, fluency and nomination on the children with choclear implant
Keywords: Leitura; Literatura infantojuvenil; Deficientes auditivos; Implantes cocleares; Reading